2022
DOI: 10.4081/pmc.2022.278
|View full text |Cite
|
Sign up to set email alerts
|

Rectovestibular fistula: Which surgical approach is suitable? A randomized controlled trial

Abstract: The management of a vestibular fistula is a challenge for pediatric surgeons. We compared four different operative techniques in terms of postoperative complications, continence, and cosmetic appearance. This prospective, randomized, comparative study included female children with rectovestibular fistulae who were selected from patients with Anorectal Malformations (ARMs) treated between January 2016 and July 2020. The patients were randomly divided into four groups based on the operative technique: Trans-Sphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…With long-term follow-up, constipation improved with age. This observation was also supported by other reports [25,41,49].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…With long-term follow-up, constipation improved with age. This observation was also supported by other reports [25,41,49].…”
Section: Discussionsupporting
confidence: 91%
“…They were all due to poor parent compliance with the postoperative home 10 anal dilatation protocol. Reported rates of anal stricture from 0 to as high as 26% are reported in the literature (25,38,47). Wehrli L. et al, 2022, in a retrospective study, reported a 0 anal stricture in 84 children with different ARMs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations